Factors Influencing Cash Holding In Property, Real Estate And Construction Companies - Nurainun Bangun; Khairina Natsir; Ngadiman Ngadiman (Jurnal Akuntansi, 2023)
This study aims to “examine academically the relationship between operating cash flow, growth opportunity, and financial distress on the company's cash holding. 43 samples were taken from 79 of property, real estate and construction sector companies on the IDX period 2018 to 2021. Data analysis began with the multicollinearity and heteroscedasticity test. After that, a hypothesis test was carried out which consisted of a t-test and an R2 test. The analysis was performed using Multiple Regression Model. The findings from this study are growth opportunity and operating cash flow have a positive effect on the company's cash holding, while financial distress has a negative effect on cash holding. The implication of this finding is that companies need to control the amount of cash holding so that the amount of cash supply in the company can be maintained at an optimal point so that the company can avoid bankruptcy.”